System-concept and features of the developmental training content of Mathematics (Pedagogy of Higher and Secondary Education, 2015)
Semenets S. P. System-concept and features of the developmental training content of Mathematics.In the paper the concept of the term system-concept is defined, the basic requirements for the developmental training content of Mathematics, ensuring the achievement of the goals of personal development subjects of teaching and mathematical activity are represented. According to the results of the theoretical analysis the basic conceptual positions of the developmental training content of Mathematics are defined.
Keywords: system-concept; a mathematical model; the content of training; developmental training of Mathematics